1997
DOI: 10.1038/bjc.1997.547
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent pattern of chromosomal aberrations and immunophenotypic appearance defines anal squamous cell carcinomas

Abstract: Summary Squamous cell carcinomas of the anus are rare neoplasias that account for about 3% of large bowel tumours. Infections with human papillomaviruses are frequently detected in these cancers, suggesting that pathogenic pathways in anal carcinomas and in carcinomas of the uterine cervix are similar. Little is known regarding recurrent chromosomal aberrations in this subgroup of squamous cell carcinomas. We have applied comparative genomic hybridization to identify chromosomal gains and losses in 23 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…These data support gain of 3q as an important event in the oncogenesis of HPV-related SCCs since, in a previous study, we have shown that a similar proportion of stage 1b HPV-positive cervical SCCs harbour 3q gain (Allen et al, 2000). Gain of 3q has also been detected by others in cervical SCCs (Heselmeyer et al, 1996(Heselmeyer et al, , 1997bDellas et al, 1999;Kirchoff et al, 1999) and in HPV-positive SCC of the anus and its precursor lesions (Heselmeyer et al, 1997a;Haga et al, 2001). Further, we were able to map the smallest region of gain in vulvar SCCs to 3q22 -25, whilst our previous series of cervical cancers showed the smallest area of gain to be 3q24 -26 (Allen et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…These data support gain of 3q as an important event in the oncogenesis of HPV-related SCCs since, in a previous study, we have shown that a similar proportion of stage 1b HPV-positive cervical SCCs harbour 3q gain (Allen et al, 2000). Gain of 3q has also been detected by others in cervical SCCs (Heselmeyer et al, 1996(Heselmeyer et al, , 1997bDellas et al, 1999;Kirchoff et al, 1999) and in HPV-positive SCC of the anus and its precursor lesions (Heselmeyer et al, 1997a;Haga et al, 2001). Further, we were able to map the smallest region of gain in vulvar SCCs to 3q22 -25, whilst our previous series of cervical cancers showed the smallest area of gain to be 3q24 -26 (Allen et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, a more recent study un-ambiguously established the central role of 3q for progression from low-grade dysplastic lesions to higher grades and to invasive carcinomas and showed that the gain of 3q can occur in morphologically normal Pap smears of women who developed cervical carcinomas after only a short latency . Gain of chromosomal region 3q is also recurrently observed in other types of cancer, including tonsillar cancer and carcinomas of the anogenital region that are both associated with HPV DNA (Heselmeyer et al, 1997b;Dahlgren et al, 2003;Stoltzfus et al, 2005).…”
mentioning
confidence: 99%
“…In sporadic colorectal cancer, MSI is seen in approximately 15% of cases. The prevalence of MSI in sporadic anal carcinoma is less clear with most studies describing loss of heterozygosity (LOH) at chromosomes 5p, 11q and 18q in relation to integration of HPV DNA and subsequent expression of E6 and E7 genes [27,28]. To our knowledge, there are no reports describing the prevalence of MSI in anal cancer.…”
Section: Introductionmentioning
confidence: 99%